(untitled) (Palimpsesto, 2021)
This paper aims to reflect about cultural management as a tool to resist the hegemonic dynamics of capitalism, and the role of the community-engaged art as instrument for creating community identity. At first, the concepts of hegemony and symbolic violence and their relationship with culture are analysed; then, the challenges and contradictions in the enlargement of artistic repertoires are discussed; finally, this paper focuses on the community construction of the symbolic, to think the political character of cultural management.